(untitled) - James A. Hall; James A. Hall; Tommie Singleton (Mason, Ohio, 2005)
IT AUDITING is an innovative and cutting edge product, which provides students an understanding of how to audit accounting information systems, including such new and expanded coverage of enterprise systems, fraud and fraud detection topics as continuous online auditing. Its organization and its integration of ACL software within the package ensure a solid background in traditional auditing as well as in the auditing of accounting information systems. The combination of text and software create a double learning environment in which students will gain a true understanding of how these audits take place in the real world
Keywords: Electronic data processing